2020
DOI: 10.2147/ott.s243221
|View full text |Cite
|
Sign up to set email alerts
|

<p>MicroRNA-374b-5p Functions as a Tumor Suppressor in Non-Small Cell Lung Cancer by Targeting FOXP1 and Predicts Prognosis of Cancer Patients</p>

Abstract: Background: Lung cancer remains the most frequent malignancy worldwide with increasing morbidity and mortality. This study aimed to assess the expression of microRNA-374b-5p (miR-374b-5p) in tissues and cell lines of non-small cell lung cancer (NSCLC) and to evaluate the prognostic value of miR-374b-5p as well as its biological function in tumor progression. Materials and Methods: Expression of miR-374b-5p in NSCLC patients and cells was estimated using quantitative real-time PCR. The prognostic value of miR-3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…In this study, miR ‐ 374b ‐ 5p was downregulated in glioma, which revealed its function as a tumour suppressor. Similarly, miR ‐ 374b ‐ 5p targets FOXP1 and exerts a protective role in non–small‐cell lung cancer and ovarian cancer 47,48 . Additionally, both miR ‐ 374b ‐ 5p and miR ‐ 454 ‐ 3p exert inhibitory effects by regulating ZEB2 in bladder cancer 49 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, miR ‐ 374b ‐ 5p was downregulated in glioma, which revealed its function as a tumour suppressor. Similarly, miR ‐ 374b ‐ 5p targets FOXP1 and exerts a protective role in non–small‐cell lung cancer and ovarian cancer 47,48 . Additionally, both miR ‐ 374b ‐ 5p and miR ‐ 454 ‐ 3p exert inhibitory effects by regulating ZEB2 in bladder cancer 49 .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, miR ‐ 374b ‐ 5p targets FOXP1 and exerts a protective role in non–small‐cell lung cancer and ovarian cancer. 47 , 48 Additionally, both miR ‐ 374b ‐ 5p and miR ‐ 454 ‐ 3p exert inhibitory effects by regulating ZEB2 in bladder cancer. 49 Moreover, miR ‐ 374b targets FOXM1 , and its overexpression mediates adverse effects in cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
“…At present, miR-374b-5p, miR-196a-5p, miR-138-5p, miR-150-5p, miR-196b-5p, miR-320a, miR-186-5p, etc. were related to the progress of NSCLC (30)(31)(32)(33)(34)(35)(36)(37)(38). For example, miR-138-5p could reduce the growth of NSCLC cells and increase the number of tumor-infiltrating dendritic cells (DCs).…”
Section: Discussionmentioning
confidence: 99%
“…These results give evidence that hsa-miR-374-5p binds to the that quantified luciferase activity to validate the regulatory effect of miRNAs. 31,32 This indicated that the miRNA-mediated suppression is exerted at the mRNA level, probably by mRNA degradation, and not on the protein level through translational repression.…”
Section: F I G U R Ementioning
confidence: 99%